Krisis Efektivitas Bimbingan dan Konseling di Sekolah: Ketika Konselor Menjadi Generalis Tanpa Spesialis : The Crisis of Effectiveness of Guidance and Counseling in Schools: when Counselors Become Generalists without Specialization - Astrid Apandi; Aswar, Aswar (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
Guidance and Counseling (BK) is a crucial component of the education ecosystem, supporting students' academic, socio-emotional, and career development. However, the effectiveness of BK services in schools is often suboptimal due to counselors' overly generalist roles and lack of in-depth specialization. This article aims to analyze the root causes of ineffective BK services due to unspecialized competencies, and to identify opportunities and challenges for the BK profession. The research method used was a systematic literature review (SLR) of relevant national and international articles. The study results indicate that a lack of competency focus leads to low-quality interventions, weak service management, and limited evidence-based practices. Furthermore, challenges such as administrative workload, lack of professional development, and limited resources exacerbate the situation. Conversely, significant opportunities arise through the MTSS approach, strengthening BK management, and developing specializations based on student needs. This article offers comprehensive solutions that include strengthening competencies, restructuring services, and improving data-driven